Vítimas de trauma crânio-encefálico e seu retorno a produtividade após 6 meses e 1 ano Head injury victms and their return to productivity after 6 months and 1 year - Regina Marcia Cardoso de Sousa; Maria Sumie Koizumi (SciELO, 1999)
Trata-se de um estudo prospectivo que analisa o ,retorno a produtividade de vítimas de trauma crânio-encefálico (TCE) de diferentes gravidades, com idade entre 12 e 6C anos. As vítimas foram examinadas aos 6 meses e 1 ano pós-trauma e seu retorno à produtividade foi analisado, considerando as variáveis nível de escolaridade e tipo de ocupação anterior ao trauma. A maioria (73,6%) retornou a atividade produtiva aos 6 meses e a freqüência de retorno à produtividade foi aior 1 ano após TCE. Quanto ao retorno ao trabalho remunerado e nível de escolaridade ou tipo de ocupação anterior, não houve associação estatística significativa. A prospective and longitudinal study about head injury victims was carried out in order to identify their return to productivity after 6 months and 1 year post-trauma and to analyze the relationship between their return to work and their educational level as well as to determine the relationship between their return to .work and their type of job before the onset of the injury. Of the 72 patients who were students or employees pre-injury, or housewives at the time of injury, the majority (73,6%) had returned to productivi:'y 6 months after onset of injury. Of the victims who had returned to roductivity, 25.0% had changed their original occupations or reported significant problems when returning to productivity. Baseline return was achieved in 48.6% of the victims at 6 months. Return to productivity was higher at 1 year after injury than at 6 months. When. the relationship between return to work and educational level and job type was analyzed, return to work was not related to educational level or job type.